The umpA gene of Escherichia coli encodes phosphatidylglycerol:prolipoprotein diacylglyceryl transferase (lgt) and regulates thymidylate synthase levels through translational coupling. - Gan, K (1995)
Using a combination of biochemical, physical, and genetic techniques, we have shown that the umpA gene of Escherichia coli is allelic with the lgt (phosphatidylglycerol:prolipoprotein diacylglyceryl transferase) of Salmonella typhimurium. These genes are essential for the viability of the respective organism and exhibit 92.8% sequence identity at the amino acid level. In E. coli, lgt and thyA (thymidylate synthase) form an operon. Thymidylate synthase levels are regulated by transcription from the lgt promoter and by translational coupling.